2015
DOI: 10.3109/00498254.2014.1003113
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory mechanisms of celastrol on human liver cytochrome P450 1A2, 2C19, 2D6, 2E1 and 3A4

Abstract: 1. The present study was conducted to examine the possibility of herb-drug interaction by celastrol, which is a main compound isolated from Tripterygium wilfordii Hook F. using human liver microsomes with cocktail methods. Focused on its inhibitory manner on the metabolism of model probe substrates of five cytochrome P450 isoenzymes (CYP1A2, CYP2C19, CYP2D6, CYP2E1 and CYP3A4) in vitro which are important with the metabolism of different xenobiotics. 2. The results showed that celastrol inhibited the five type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…A single dose of Apa increased the AUC (0‐t) , AUC (0‐∞) and Cmax of Ven significantly, while Vz/F and CLz/F were decreased, indicating inhibition of Apa on Ven. The in vitro study also indicated that the inhibitory effect of Apa on Ven in RLM and HLM was both strong with IC 50 <10 μM , making a good accordance with the in vivo pharmacokinetics study. Interestingly, the influence of multiple dose of Apa on Ven was not that obvious, with only CLz/F decreased and Cmax increased.…”
Section: Discussionsupporting
confidence: 74%
“…A single dose of Apa increased the AUC (0‐t) , AUC (0‐∞) and Cmax of Ven significantly, while Vz/F and CLz/F were decreased, indicating inhibition of Apa on Ven. The in vitro study also indicated that the inhibitory effect of Apa on Ven in RLM and HLM was both strong with IC 50 <10 μM , making a good accordance with the in vivo pharmacokinetics study. Interestingly, the influence of multiple dose of Apa on Ven was not that obvious, with only CLz/F decreased and Cmax increased.…”
Section: Discussionsupporting
confidence: 74%
“…Pharmacokinetic investigations indicated that celastrol is poorly absorbed and the bioavailability of celastrol is low [6][7][8]. The metabolic profile of celastrol has been investigated [9][10][11]. However, little information is available regarding the intestinal absorption mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…That is to say, the hepatotoxicity caused by celastrol is directly related to its accumulation in the liver cells. To be an inhibitor of CYP450s [35], celastrol could worsen hepatotoxicity caused by triptolide. As mentioned before, triptolide (not more than 10 μg) is used as the quality control and limited indicator for Tripterygium polycoride tablets, due to the presence of plentiful celastrol, it could lower the minimum concentration of triptolide that leads to decreased cell viability.…”
Section: Discussionmentioning
confidence: 99%